Hepatitis B : the hunt for a killer virus - Blumberg, Baruch S., 1925-2011 (Princeton University Press, 2002)
About 375 million people are infected with the hepatitis B virus. It has killed more people than AIDS and also causes millions of cases of liver cancer. The discovery of this deadly virus and the vaccine against it--a vaccine that is sharply decreasing the infection rate worldwide and is probably the first effective cancer vaccine--was one of the great triumphs of twentieth-century medicine. And it almost didn't happen. With wit and insight, this scientific memoir and story of discovery describes how Baruch Blumberg and a team of researchers found a virus they were not looking for and created a vaccine for a disease they previously knew little about--work that took the author around the world and won him the Nobel Prize. Blumberg and his collaborators were investigating relationships between gene distribution and disease susceptibility, research that was yielding interesting data but no real breakthroughs. Many viewed their work as more field trip than science. But, through decades of hard work and investigative twists and turns, their pursuit led to the hepatitis B antigen, the elusive virus itself, and, ultimately, the vaccine. As he takes the reader through the detective work that culminated in his incredible discovery, the author recounts with immediacy exciting moments in the lab and in the field--from a hair-raising flight to Africa to an unpleasant encounter with Alaskan sled dogs. The hepatitis B story is more than a fascinating chronicle of a major discovery. What Blumberg followed to the virus was a trail of remarkable "accidents" that happen when scientists seek answers to interesting questions. Those events, combined with the investigator's determined persistence, resulted in studies that generated a pharmaceutical industry, have far-flung public-health applications, and saved millions of lives.